Are Unnecessary Serial Radiographs Being Ordered in Children with Distal Radius Buckle Fractures? - Shi-Neng James Ling; Aidan J. Cleary (Radiology Research and Practice)
Background. Torus or buckle distal radius fractures are common injuries in the pediatric population. By definition, they are stable and can be treated conservatively with a wrist splint or soft crepe bandage. Objective. The objective of this study was to evaluate the utility of serial radiographs in the clinical outcome of children with stable distal radius buckle fractures. Materials and Methods. A one-month retrospective analysis was undertaken at two major hospitals in Queensland—Logan and Redlands Hospital. Statistical analysis was performed to identify any relationships between serial radiographs and certain demographic parameters including fracture characteristics, age, sex, and limb side. Results. Of the 136 patients, 50% had more than one radiograph series taken. A total of 576 single radiographs and 251 radiograph series were taken. All fractures healed without complications and did not require active intervention. There was a statistically significant relationship (p=0.0015) between fracture angulation and multiple radiographs series. A cost analysis revealed $55,890 per year could be saved by not performing serial radiographs. Conclusion. Serial radiographs did not appear to change the excellent clinical outcome for children with distal radius buckle fractures. There is a potential to reduce costs and prevent unnecessary ionizing radiation exposure to children.